2008
DOI: 10.1007/s00264-008-0659-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for pulmonary embolism after hip and knee arthroplasty: a population-based study

Abstract: Pulmonary embolism (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(63 citation statements)
references
References 34 publications
(30 reference statements)
2
57
1
Order By: Relevance
“…Considering the burden of these diseases within the older population, it is not surprising that among all comorbidities, cardiovascular diseases present the most significant risk for VTE. However, in contrast to our results, some investigators have reported that coronary artery disease is a poor predictor of VTE, or can even diminish the risk of VTE [9,11], possibly due to general better health in the populations of these countries or stricter criteria for monitoring and treatment of cardiovascular diseases, including earlier aggregation therapy. The limitations of our study are the relatively small number of patients with follow-up only during the hospitalisation period.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Considering the burden of these diseases within the older population, it is not surprising that among all comorbidities, cardiovascular diseases present the most significant risk for VTE. However, in contrast to our results, some investigators have reported that coronary artery disease is a poor predictor of VTE, or can even diminish the risk of VTE [9,11], possibly due to general better health in the populations of these countries or stricter criteria for monitoring and treatment of cardiovascular diseases, including earlier aggregation therapy. The limitations of our study are the relatively small number of patients with follow-up only during the hospitalisation period.…”
Section: Discussioncontrasting
confidence: 56%
“…Most cases of symptomatic VTE present following discharge from hospital and often result in hospital readmissions [5], although VTE can often be asymptomatic and the first signs of a PE can be sudden death. With this in mind many surgeons now administer prolonged thromboprophylaxis, and there have been significant advances in the use of regional anaesthetic techniques and oral pharmacological anticoagulants [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Older age, female gender, obesity, underlying disease, type of anesthesia, simultaneous bilateral THAs, surgical approach, and prolonged immobilization in bed are known risk factors for DVT and PE in studies of patients from Western countries [2,19,21,30]. After multivariate analysis in this study, prolonged immobilization was identified as a risk factor for DVT.…”
Section: Discussionmentioning
confidence: 86%
“…The effects of obesity on outcomes such as venous thromboembolism (VTE), wound complications, infection, and bleeding in patients undergoing total joint arthroplasties have been documented in numerous studies [4,6,7,13,15,18,20,21]. However, large studies to determine the effect size of morbid obesity on early postoperative complications after THA or TKA are lacking.…”
Section: Introductionmentioning
confidence: 99%